Digital urbanisms: Exploring the spectacular, ordinary and contested facets of the media city - Vuolteenaho,Jani (2015)
This introductory review article develops an analytic-conceptual distinction between spectacular, ordinary and contested facets of the present-day digitized urban condition. We reject a scholarly techno-optimism versus techno-pessimism dichotomy and argue that this triadic conceptualization can pave the way for a better understanding of the multiple, often contradictory and unpredictable implications of the fast-proceeding digitalization on cities and people who inhabit them. First, we discuss the intensified spectacularization from the perspective of labeling of cities as technologically advanced smart spaces and endeavors to enhance the attractiveness and ICT-glamour of urban public spaces. Next, we highlight two acute ordinary sides of living in digitally-mediated cities: the contributions of code-based software and digital media infrastructures to the routinized practices of urban life, and the escalation of the perceived standards of what constitutes the ordinary in the face of rapid technological change. Thirdly, we shed light on attempts at re-igniting street-level political agency, and the creation of outside-the-mainstream public spheres, via the aid of digital technology. In the end of the article, we consider how variable spectacular, ordinary and contested facets of the media city are co-present in the following articles of this Special Issue.